Acculturation as translation: mimicry, satire and resistance in Chewa dance - Nthala, Grant (University of the Free State, 2012)
communities of Malawi, Zambia, Mozambique, Tanzania and Zimbabwe. With this particular dance – and indeed with many others – historical connotations, cultural reverberations, and systemic institutionalisation come into play. The hierarchical organisation of the Chewa dance systems and the orderly and enigmatic tendencies of the dance displays are reminiscent of historical phenomena linked to the Chewa diaspora. In essence, mimicry, satire and other forms of enactment (often dramatic) in Chewa dance subtly or candidly unearth acculturative elements within the Chewa ethnicity. This article seeks to illustrate that the Chewa dances gulewamkulu and mganda constitute theatre and that their performance demonstrates a manifestation of traditional Chewa cultural features that have been altered or modified by borrowing from or adapting to other Bantu-related and European cultures.

Die gulewamkulu maskerdans is die belangrikste Chewa-dans wat in alle Chewa-gemeenskappe in Malawi, Zambië, Mosambiek, Tanzanië en Zimbabwe uitgevoer word. Met hierdie dans – soos ook in die geval met andere – geld historiese konnotasies, kulturele weerklanke, asook sistemiese institusionalisering. Die hiërargiese organisies van die Chewa-danssisteme en die ordelike en enigmatiese tendense van die dansuitvoerings herinner aan historiese fenomene wat met die Chewa-diaspora verband hou. In wese openbaar mimiek, satire en ander vorme van spel (dikwels dramaties) in Chewa-dans akkulturatiewe elemente binne Chewa-etnisiteit op ’n subtiele of openlike wyse. Hierdie artikel wil illustreer dat die Chewa-danse gulewamkulu en mganda ’n vorm van teater uitmaak, en dat die uitvoering daarvan ’n manifestasie van tradisionele Chewa kulturele kenmerke demonstreer deur middel van ’n ontlening aan of verwerking van ander Bantoe-verwante of Europese kulture.
Keywords: Gulewamkulu; Chewa dance; Culture; Mganda